Myanmar's Mountain and Maritime Borderscapes : Local Practices, Boundary-Making and Figured Worlds - Oh, Su-Ann, 1973- (Book collections on Project MUSE., 2016)
This edited volume adds to the literature on Myanmar and its borders by drawing attention to the significance of geography, history, politics and society in the construction of the border regions and the country. First, it alerts us to the fact that the border regions are situated in the mountainous and maritime domains of the country, highlighting the commonalities that arise from shared geography. Second, the book foregrounds socio-spatio practices--economic, intimate, spiritual, virtual--of border and boundary-making in their local context. This demonstrates how state-defined notions of territory, borders and identity are enacted or challenged. Third, despite sharing common features, Myanmar's borderscapes also possess unique configurations of ethnic, political and economic attributes, producing social formations and figured worlds that are more cohesive or militant in some border areas than in others. Understanding and comparing these social practices and their corresponding life-worlds allows us to re-examine the connections from the borderlands back to the hinterland and to consider the value of border and boundary studies in problematizing and conceptualizing recent changes in Myanmar.